2010
DOI: 10.1590/s0100-83582010000500016
|View full text |Cite
|
Sign up to set email alerts
|

Residual activity of herbicides used in soybean agriculture on grain sorghum crop succession

Abstract: -The sorghum is a kind of prominence before the cultures used in succession in the Brazil. However, little information concerning the effects of residual activity of herbicides on the crop in this region are known. The objective of this study was to evaluate the residual activity of herbicides used in weed management in soybeans as well as check their effects on grain sorghum grown in succession. For the field experiment, we used a randomized block design with four replications. Eight herbicide treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
0
13
0
16
Order By: Relevance
“…No Brasil, o P. Glaucum e o Sorghum bicolor foram altamente afetados quando cultivados em sucessão a soja, que recebeu aplicação em pré-emergência do sulfentrazone (DAN et al, 2010;DAN et al, 2011).…”
Section: Resultsunclassified
“…No Brasil, o P. Glaucum e o Sorghum bicolor foram altamente afetados quando cultivados em sucessão a soja, que recebeu aplicação em pré-emergência do sulfentrazone (DAN et al, 2010;DAN et al, 2011).…”
Section: Resultsunclassified
“…Herbicides that have a long residual effect on the soil can cause carryover problems, making it infeasible to grow sensitive species in succession, which is the case of sulfentrazone (Artuzi & Contiero, 2006;Dan et al, 2010). Moreover, the permanence of the product in the soil for a long time (Blanco et al, 2010) increases the risks of leaching (Melo et al, 2010a) and contamination of groundwater (Santos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dan et al (2010) evaluating the effect of several pre-emergent herbicides (including diclosulam at the dosage of 35 g ha -1 ) on weed control in soybean crop and the subsequent effect on successor crop (sorghum), observed that these class of herbicides showed high persistence in soil (diclosulam up to 87 days) and can cause injuries in subsequent crops.…”
Section: Introductionmentioning
confidence: 99%
“…This herbicide has excellent pre-emergent activity in soil to control of several dicotyledonous and some monocotyledon weeds, being widely used in the control of plants resistant to ALS inhibitors (Blanco et al, 2010). Dan et al (2010) studying the action of pre-emergent herbicides, verified that the residual activity of sulfentrazone was high, exceeding 200 days, which may cause damage to subsequent crops.…”
Section: Introductionmentioning
confidence: 99%